2018
DOI: 10.1016/j.evolhumbehav.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in political leadership in an egalitarian society

Abstract: We test the contribution of sex differences in physical formidability, education, and cooperation to the acquisition of political leadership in a small-scale society. Among forager-farmers from the Bolivian Amazon, we find that men are more likely to exercise different forms of political leadership, including verbal influence during community meetings, coordination of community projects, and dispute resolution. We show that these differences in leadership are not due to gender per se but are associated with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 97 publications
7
93
2
Order By: Relevance
“…Thus, men may have evolved a stronger drive to acquire shareable resources. Support for this idea comes from anthropological studies that indicate sex differences in the division of labor, where men more often than women pursue highrisk activities to acquire resources (Hawkes, O'Connell, & Blurton Jones, 2001;Von Rueden, Alami, Kaplan, & Gurven, 2018). Obviously, the first transfer in the trust game and the second transfer in the gift-exchange game are excellent opportunities for resource acquisition as in both cases the initial number of resources is multiplied.…”
Section: Reconciling the Results From The Two Gamesmentioning
confidence: 99%
“…Thus, men may have evolved a stronger drive to acquire shareable resources. Support for this idea comes from anthropological studies that indicate sex differences in the division of labor, where men more often than women pursue highrisk activities to acquire resources (Hawkes, O'Connell, & Blurton Jones, 2001;Von Rueden, Alami, Kaplan, & Gurven, 2018). Obviously, the first transfer in the trust game and the second transfer in the gift-exchange game are excellent opportunities for resource acquisition as in both cases the initial number of resources is multiplied.…”
Section: Reconciling the Results From The Two Gamesmentioning
confidence: 99%
“…If the results support Hypotheses 1 and 2, the next step is to provide evidence that demonstrates the potential role of evolutionary forces in gendered leadership preferences by establishing a link from intergroup threat through preferences for leader physical formidability to preferences regarding the biological sex of a preferred leader. Evidence suggests that part of the male advantage in leadership attainment is related to males' greater body size and physical strength (e.g., Handwerker and Crosbie, 1982;Glowacki and von Rueden, 2015;von Rueden et al, 2018; but see Low, 1992). Overall, the analyses presented here suggest:…”
Section: Evolutionarily Informed Demand Factorsmentioning
confidence: 57%
“…This, of course, includes humans. For instance, Brown (1991, 137) states that "In the public political sphere men form the dominant element among [every people or people in general]" (see also Ludwig, 2002;von Rueden et al, 2018). Archeological and anthropological data suggest that human males have been vastly over-represented in the public sphere dating back thousands of years to Egyptian pharaohs; Chinese, Japanese, and Roman emperors; Catholic Popes; and European monarchs (Murray and Murray, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to humans, von Rueden et al. () found that among the Tsimane—egalitarian forager‐farmers of the Bolivian Amazon—men's greater political influence stemmed in part from sex differences in body size, parental investment costs, and division of labor but was also due to the increased access to cooperative partners that these latter characteristics beget.…”
Section: Grounded In Evolutionary Theorymentioning
confidence: 99%